2022
DOI: 10.1007/s00277-022-05059-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the nutritional risk index in patients with newly diagnosed multiple myeloma

Abstract: The nutritional risk index (NRI), which is based on weight and albumin levels, is closely associated with the prognosis of many cancers. However, its prognostic value has not been investigated in patients with newly diagnosed multiple myeloma (NDMM). We aimed to assess the association between the NRI and survival outcomes in patients with NDMM. We retrospectively collected and analyzed clinical and laboratory data from patients with NDMM between 2005 and 2019 at our center. Patients were stratified into the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The major downside is that these parameters alone can easily be swayed by non-nutritional factors such as hydration status [9], which is likely inaccurate in haematological cancer due to large intravenous infusions during treatment and changes in organ function [10]. Other combined parameters such as patient-generated subjective global assessment (PG-SGA) [5,11], Nutrition Risk Index(NRI) [12], and Controlling Nutritional Status (CONUT) [13] are attempted to permit more accurate risk strati cation, but the weakness is comparatively di cult to use and nutrition training is needed [14]. Besides, previous studies mainly focus on single diagnosis (acute leukaemia mostly) and thus can be incomprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…The major downside is that these parameters alone can easily be swayed by non-nutritional factors such as hydration status [9], which is likely inaccurate in haematological cancer due to large intravenous infusions during treatment and changes in organ function [10]. Other combined parameters such as patient-generated subjective global assessment (PG-SGA) [5,11], Nutrition Risk Index(NRI) [12], and Controlling Nutritional Status (CONUT) [13] are attempted to permit more accurate risk strati cation, but the weakness is comparatively di cult to use and nutrition training is needed [14]. Besides, previous studies mainly focus on single diagnosis (acute leukaemia mostly) and thus can be incomprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have confirmed that baseline nutrition status is a common factor associated with decreased overall survival time in patients with HMs undergoing chemotherapy and allogeneic hematopoietic cell transplantation (HCT) (10)(11)(12)(13)(14). Moreover, it has been proposed that nutritional treatment would improve the prognosis in patients with HMs before HCT (15).…”
Section: Introductionmentioning
confidence: 99%